Assessing the Coverage of Urban Green Space in Butwal Sub-Metropolitan City, Nepal: A GIS based Approach - Thapa, Mahendra Singh; Poudel, Gokul (Forestry: Journal of Institute of Forestry, Nepal, 2018)
Urban green spaces are integral part of urban infrastructure. Green spaces can offer a number of benefits ranging from inner spiritual to outer materialistic values. Available green spaces in particular area especially in urban places need to be identified and located properly with scientific way and means so that we can use those places in emergency caused by natural or human induced hazards. This study has tried to measure the green space available for people dwelling in Butwal Sub-Metropolitan City of Nepal. An attempt was made to quantify green spaces in urban environments from Landsat 8 OLI imageries using object-oriented approach and field verification. The study concluded that the total green space available in Butwal Sub-Metropolitan City is 86.37 km2 i.e., around 86% of total municipal area and per capita green space is around 623 m2.